Follow the fleet [1936] - Sandrich, Mark ([s.l.] : Universal Studios, 2005)
Two navy men (Fred Astaire and Randolph Scott) have just docked in San Francisco after extended sea duty. They decide to spend their shore leave at a local dancehall where one man is surprised to find his ex-vaudeville partner (Ginger Rogers). The other man steals the heart of the partner's sister. Includes small roles by Betty Grable and Lucille Ball.
film
Keywords: Sandrich, Mark